"In the centre of a circle": Olive Moore's Spleen and Gestational Immigration. Issue 1 (4th May 2018) - Kingsley, Erin M.
ABSTRACT: In Olive Moore's 1930 novel Spleen, the experience of exile and immigration cannot be separated from the modernist narrative of pregnancy and childbirth. The novel pivots on the binary idea of the center versus the periphery, and its primary modality is the shuttling movement between power and the lack of power (symbolized by a circle and its center versus periphery). The aesthetics of instability this movement creates forms a foundational sense of "gestational immigration" – the physical and psychological movement that occurs when one becomes a mother. Viewing Spleen through the lens of gestational immigration, this essay explores the novel's complex investment in rupture and unfolding, and its potential to trouble fixed categories like pregnancy, woman, immigrant, other.